An Incarcerated Colon Inguinal Hernia That Perforated into the Scrotum and Exhibited an Air-Fluid Level - Seisuke Ota; Toshio Noguchi; Tomoya Takao; Takumi Sakamoto; Yuichiro Kanie; Ken-ichi Omae; Shunji Fujie; Yoshiaki Kanaya; Akinori Kasahara; Tadashi Matsumra (Case Reports in Medicine)
There are few reports of a transverse colon inguinal hernia; furthermore, an inguinal hernia perforating the scrotum is rare. Here we report the case of a 79-year-old man who died after developing an incarcerated colon inguinal hernia that perforated the scrotum and exhibited an air-fluid level. The patient was referred to our hospital in November 2011 with a complaint of inability to move. Physical examination revealed an abnormally enlarged left scrotum and cold extremities. He reported a history of gastric cancer that was surgically treated more than 30 years ago. His white blood cell count and C-reactive protein level were elevated. Abdominal and inguinal computed tomography revealed that his transverse colon was incarcerated in the left inguinal canal. Free air and air-fluid level were observed around the transverse colon, suggestive of a perforation. The patient and his family refused any surgical intervention; therefore, he was treated with sultamicillin tosilate hydrate and cefotiam hydrochloride. However, he succumbed to panperitonitis 19 days after admission. The findings from this case indicate that the transverse colon can perforate into an inguinal hernia sac.